Temporal and spatial dynamics of pulse production in India - Sekar, Inba; Roy, Devesh; Joshi, Pramod Kumar (International Food Policy Research Institute, 2017)
Chapter 3 gives a detailed description of pulse production dynamics across regions and over time. It divides the history since 1960 into four time periods: pre– and early Green Revolution; advanced and post– Green Revolution; postliberalization; and post– trade spike. To study the spatial movement in pulse cultivation, states are grouped into five geographic zones: north, east, south, west, and central. The chapter formally establishes that pulse production has shifted from traditional to nontraditional areas over time, moving from north to south and from east to west and central regions, with Madhya Pradesh and Chhattisgarh becoming the hub of pulses production.